Calendar interviewing: a mixed methods device for a biographical approach to migration. Issue 1 (2nd January 2017) - Barbeiro, Ana; Spini, Dario
ABSTRACT: Biographical interviews are used in life stories research to elicit narratives on retrospective views of the self and the social world. Life calendars are used in life course research to collect standardized data in various domains of individual lives. Both instruments deal with autobiographical memory, which is a critical aspect for data quality and accuracy. This article presents a mixed methods use of life calendars and life stories for researching on migration called the Calendar Interviewing Device (CID). The CID consists of a life calendar for characterizing trajectories and collecting life stories through open-ended interviews. An analysis of 12 interviews examines the features of this particular research device, namely its flexibility on adapting to different interviewees, the strategies they used for recalling events and locating them in time, and the richness of the data obtained with the CID.